Studi Komparatif: Analisis Konsep Mubtada’ dan Khabar pada Gemini AI berdasarkan Kitab Mulakhkhaṣ Fuad Ni‘mah - Rosy Puspita Sari; Siti Nurdinah (Institut Muslim Cendekia, 2026)
Research on the utilization of Artificial Intelligence (AI) in Arabic language learning has continued to grow alongside the increasing integration of digital technologies in education. The emergence of AI systems such as Google Gemini offers new opportunities to support the learning of Arabic grammar (nahwu), yet the accuracy of the information generated by these systems must be evaluated against authoritative grammatical sources. Therefore, this study aims to analyze the accuracy of the concepts of mubtada’ and khabar as generated by Gemini AI by comparing its explanations with the principles of Arabic grammar presented in Mulakhkhas Qawaʿid al-Lughah al-‘Arabiyyah by Fu’ad Ni‘mah. This study employed a descriptive qualitative approach using a comparative method based on library research. The primary data consisted of structured responses generated by Gemini AI regarding the definitions, classifications, and examples of mubtada’ and khabar. Secondary data were obtained from Mulakhkhas Qawaʿid al-Lughah al-‘Arabiyyah, which served as the main reference source. The findings indicate that Gemini AI demonstrates a relatively high level of accuracy in explaining the basic definitions and general classifications of mubtada’ and khabar. However, the reference text provides more comprehensive explanations, particularly concerning syntactic functions, detailed classifications, and specific grammatical conditions. These findings suggest that AI has considerable potential as a supplementary learning tool in Arabic grammar instruction; nevertheless, its outputs should be verified against authoritative grammatical references to ensure accuracy and depth of understanding.